Expanding Analytical Perspectives on Children's Picturebook Apps. (November 2016) - Aguilera, Earl; Kachorsky, Dani; Gee, Elisabeth; Serafini, Frank
Research on the nature and impact of book apps or e-reading in general is still limited and informed by diverse assumptions about the nature of these new "texts, " the varied forms of engagement and meaning-making associated with them, and their implications for understanding literacy and learning in the digital age. The purpose of this article is to explore the affordances and constraints inherent in an examination of children's picturebook apps through multiple analytical frameworks—in this case drawn from social semiotics, film analysis, and game studies. After outlining these frameworks in the context of our evolving new media landscape, we move on to more detailed analyses of the children's picturebook app The Fantastic Flying Books of Mr. Morris Lessmore from each of these perspectives. We conclude with lessons that might be learned from juxtaposing these analytical frameworks and suggest implications for literacy education, research, and practice.